Urgensi Perlindungan Hak Kekayaan Intelektual di Era Digital: Strategi Hukum dalam Melindungi Ide Bisnis - Chandra Devaraihan Wahyudi; Ulfi Dwiani; Ikhwan Aulia Fatahillah (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study aims to analyze the urgency of intellectual property rights protection in the context of the digital economy and to formulate effective legal strategies for protecting business ideas. The background of this study stems from the increasing vulnerability of business ideas to imitation and infringement due to advances in digital technology, which have accelerated the distribution and reproduction of intellectual works. The method used is non-empirical legal research employing a normative, doctrinal, and conceptual approach through an analysis of relevant legislation, legal doctrines, and academic literature. The research findings indicate that although Indonesia’s legal system possesses a comprehensive regulatory framework, there remain normative gaps and inconsistencies in accommodating the protection of business ideas in the digital era. The analysis also highlights the need for an integrative legal strategy through a combination of intellectual property registration, trade secret protection, strengthening of business contracts, and the utilization of digital technology. The study’s conclusion emphasizes that effective protection requires a multidimensional approach that is adaptive to technological developments and supported by responsive legal policies.